Penerapan Simulasi K3 Berbasis Studi Kasus untuk Meningkatkan Kesadaran Keselamatan Siswa SMK Negeri 4 Palangka Raya Jurusan Geologi Pertambangan - Prasetyo, Mikhael Dendi; Tumanggor, Ronal Berkat; Azman, M. Khairul; Betwin, Agre; Nababan, Bona Fransisko; Noveriady, Noveriady; Alvionyta, Agnes; Wardani, Riana Sri (-, 2026)
Occupational safety and health (OSH) is a fundamental competency that must be mastered by vocational high school students, particularly in high-risk fields such as mining geology. One of the main problems faced by partner schools is the low level of students’ safety awareness, which is largely caused by learning methods that are predominantly theoretical and lack contextual exposure to real working conditions. This community service activity aimed to improve the safety awareness of Mining Geology vocational students through the implementation of case study-based OSH simulations. The activity was conducted using a participatory approach, consisting of the delivery of basic OSH concepts, presentation of mining accident case studies, simulation of hazard identification, and reflective group discussions. The results showed an improvement in students’ understanding of work-related risks, safety procedures, and the importance of developing a safety culture in mining activities. These findings indicate that case study-based OSH simulations are an effective strategy to strengthen safety awareness among vocational students in the mining sector.